The influence of carbon nanotubes and Mn dopant onto zinc oxide for degradation of organic pollutant model under visible light irradiation / Norfarhanah Ab Wahab - Norfarhanah , Ab Wahab (2020)
Globally untreated industrial wastewaters are contaminating soil, surface water, groundwater, and consequently, the environment. Therefore, there is a huge interest in developing efficient and effective removal methods, such as photocatalytic advanced oxidation processes (AOP) under visible light (~47% of solar irradiation). In this work, the effectiveness of Mn-doped ZnO composite decorated onto multiwall carbon nanotubes (MWCNTs) on photodegrading organic pollutants was studied. This composite was simultaneously synthesized by sol gel method. XRD was used to confirm the formation of ZnO/Mn nanocomposite and the crystalline phase changes as ZnO content decreases when other elements were added to form the nanocomposite. The diffractograms corresponded to JCPDS no. 01-079-0207, where the peaks are in agreement with the diffraction pattern of ZnO. Its crystal system was wurtize hexagonal, and its space group was P63mc. It was confirmed that the presence of the Mn dopant decreases the wide band gap of ZnO from 3.2 eV to 2.4 eV, and increased its lattice parameter, which was confirmed using UV-vis. Decorated MWCNTs was confirmed due to the increased BET surface area and decreased charge recombination from the improvement of the performance of absorbing layers via the enhancement of light absorption and electron transport in the nanocomposite. The combination of Mn/ZnO resulted in spherical-shaped particles surrounding the MWCNT, which was confirmed by the FESEM. The images showed uniformly-cylindrical particles, which were the MWCNTs, and the spherical particles, which were the Mn/ZnO. The particles in the images were 70-100 nm. The pleated structure of the MWCNTs prevents the nanoparticles from agglomerating, which enhances the dispersion of MWCNTs. The presence of ZnO and Mn and its respective corresponding qualities and molecular structures pre-and post-calcination were confirmed using the ATR-FTIR. The analyses were conducted within 400 - 4000 cm. The synthesized photocatalyst was subsequently used to degrade methyl orange (MO), which represents organic pollutants. Photocatalysts can be enhanced by increasing its surface area, improving the distribution of charge carriers, reducing agglomeration, and increasing both active sites and oxygen adsorption within the suspension. It can therefore be concluded that Mn-doped ZnO decorated onto MWCNTs degrades MO quicker than the undoped ZnO and Mn-doped ZnO when exposed to visible light.